Mega events and urban air quality improvement: A temporary show?. (20th April 2019) - Li, Boying; Wang, Feng; Yin, Haitao; Li, Xinyu
Abstract: Those opposed to hosting mega events often claim that it may lead to negative environmental outcomes. This paper investigates the environmental impact of hosting the G20 summit in Hangzhou and asks two questions: (1) has hosting the G20 summit led to urban air quality improvement and (2) if so, is this improvement a short-term or long-term phenomenon? This research uses an event study method and finds that the air quality in Hangzhou was significantly improved during the G20 period and, most importantly, this positive impact seems to be a long-term phenomenon, contrary to previous studies. A placebo analysis on a similar city does not find comparable patterns, offering empirical support for a causal explanation. This paper further analyzes the steps that Hangzhou took in preparation for the G20 summit and finds many long-term oriented measures such as technological upgrades and transition from fossil fuels to clean energies. These findings show that mega events could be used as a catalyst to overcome industrial and individual resistance in improving environmental quality. Highlights: The air quality in Hangzhou was significantly improved during the G20 period. The improvement seems to persist and the reasons are explained. Policy makers may utilize mega events for long-term environmental benefits.